Integrated Assessment of Biometric Indices and Life-history Traits of Anabas testudineus in Baluhor Oxbow Lake (Journal of the Bangladesh Agricultural University, 2026)
The freshwater climbing perch (Anabas testudineus) is highly valued in Bangladesh for economic significance and food source. Understanding the life-history traits of A. testudineus is crucial for developing effective long-term conservation and management. The present study provides a comprehensive analysis of life-history traits and biometric indices such as length-weight and length-length relationships (LWRs), and length-frequency distribution. A total of 102 specimens were collected between May and July 2025 using traditional fishing gears. Total length (TL), standard length (SL) and body weight (BW) were measured using digital slide calipers and an electronic balance. Total length of the specimens ranged from 6.96-13.49 cm and body weight varied from 9.59-35.07 g. The estimated ‘b’ values revealed a pattern of negative allometric growth (b